Relationship between pre-sarcopenia and quality of life in patients with chronic liver disease: a cross-sectional study. Issue 11 (November 2019) - Ohashi, Kazuki; Ishikawa, Toru; Imai, Michitaka; Suzuki, Mitsuyuki; Hoshii, Asami; Abe, Hiroko; Koyama, Fujiko; Nakano, Tomomi; Ueki, Aya; Noguchi, Hirohito; Hasegawa, Erina; Hirosawa, Shiori; et al.
Abstract : Aim: This study aimed to clarify the relationship between pre-sarcopenia (PS) and quality of life (QOL) in patients with chronic liver disease (CLD). Patients and methods: This cross-sectional study evaluated 335 patients with CLD. PS was diagnosed on the basis of the assessment criteria by the Japan Society of Hepatology . QOL was evaluated using the short form-36. Results: Patients' mean age was 69.52 ± 10.17 years, and 169 (50.4%) participants were men. The prevalence of PS was 53.7%. Patients were divided into the PS and non-pre-sarcopenia (NPS) groups. Patients in the PS group were older (71.84 ± 9.78 vs. 66.81 ± 9.97, P < 0.01) and mostly women (65.2 vs. 37.8%, P < 0.01) compared with those in the NPS group. QOL, physical function (38.30 ± 17.63 vs. 44.02 ± 14.76, P < 0.01), physical role functioning (RP) (40.63 ± 15.38 vs. 44.88 ± 13.89, P < 0.01), and bodily pain (BP) (48.42 ± 11.45 vs. 51.24 ± 10.19, P = 0.02) were significantly lower in the PS group than in the NPS group. Logistic regression analyses identified that the independent predictive factors for PS were female sex (odds ratio: 3.16, 95% confidence interval: 2.01–4.98; P < 0.01) and RP (odds ratio: 1.97, 95% confidence interval: 1.24–3.12; P < 0.01). Conclusion: QOL characteristics of PS patients with CLD were low physical function, RP, and BP in short form-36. In addition, social role functioning was low in the PS patients aged 65–74 years, whereas RP and BP were low in those aged at least 75 years. Female sex and RP were independent predictors of PS according to the multivariate analysis. Maintaining and increasing muscle mass in patients with CLD may contribute toward improving physical QOL.